Crack propagation at bi‐material interfaces. Issue 1 (21st October 2015) - Alam, Mahabub; Parmigiani, John P.
Abstract: There is currently a gap in the understanding of how crack propagation by intergranular versus transgranular fracture varies with changes in material properties and grain size. Much of the prior work in this area has been in terms of LEFM and criterion based on toughness alone. More recent work has shown that a toughness‐and‐strength approach is required. In this study a strength‐and‐energy approach is applied to intergranular‐versus‐transgranular fracture through a cohesive‐zone approach implemented in a finite element model. Results show that intergranular fracture becomes more likely, and has an increasing shear component, as grain toughness increases and grain stiffness and grain size decrease. These results can help guide material development. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)